The Effect of Teaching Writing Using Process-Based Approach and Product-Based Approach on the Quality Of SMA Students’ Hortatory Writing - Hendrik Johanis George Frans; Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2010)
This research entitled ‘The Effect of Teaching Writing Using Process-Based Approach and Product-Based Approach on the Quality of SMA Students’ Hortatory Exposition’ had been conducted at SMAN 12 Ambon to see how these two approaches took their effect on the samples. The research underwent three major steps: pre-test, treatment, and posttest. The sample of research was two science classes of grade eleven. These two classes chosen as the samples as their previous year achievement on English had closely similar means. Since the data distribution was normal and homogenous then the research continued by taking parametric statistics to analyse post-test so independent t-test was applied for analysing the post-test to see the effect difference. The analysis on the post-test showed that there was no effect difference on the quality of students’ hortatory exposition between the students taught using process-based approach and the students taught using productbased approach. This was caused by students’ low skill and unfamiliarity to English and the short duration of experiment.